Work Values and Career Aspirations of Women Employees in Government Hospitals in Pangasinan - Santos, Merlita Q. Ed.; Reynaldo T. Gelido, DPA, (European Journal of Multidisciplinary Studies, 2018)
This study aimed to determine and analyze the extent of practice of work values and level of career aspirations of women-employees in selected government hospitals in the fifth and sixth congressional districts of Pangasinan, Philippines. The study made use of quantitative and qualitative data and descriptive correlation that looked into the relationship between the extent of practice of work values, level of aspirations and profile characteristics. Sixty nine regular women-employees with different positions were purposively selected. Data were gathered through questionnaire and analyzed using frequency counts and percentage, average weighted mean, Wilk’s A and Pearson r. It was found in the study that women-employees a) have ages within the legal age range of government employees; attended trainings/seminars relative to their work; and have monthly income commensurate to their positions; b) always practiced the work values of punctuality, honesty, respect, cooperation and industriousness; and have high level of career aspiration; c) extent of practice of work values and level of career aspiration were comparable across age, civil status, highest educational attainment, position and monthly income’ d) encountered problems with varying degrees of seriousness in the practice of work values in their respective work places; e) that significant positive correlation existed between the women-employees’ extent of practice of work values and level of career aspiration. Generally, the work values of punctuality, honesty, respect, cooperation and industry practiced by women-employees in the performance of their job have contributed to their high level of career aspiration in their present and future career status.
Keywords: Work Values, Career Aspirations, Women Employees, Government Hospitals, Pangasinan